Students' Perception of Academic Service Management of Study Programs and Its Implications on Student Satisfaction - Andi Mardiana Paduppai; Nerru Pranuta Murnaka; Mochamad Nashrullah (Lembaga Bale Literasi, 2026)
This study aims to examine students' perceptions of academic service management within study programs and its implications for student satisfaction at Muhammadiyah University of Sidoarjo. Academic service management in this study encompasses aspects of planning, organizing, implementing, and monitoring and evaluating academic services. The study used a quantitative approach with a descriptive and correlational design. The subjects were active students at Muhammadiyah University of Sidoarjo. were selected as respondents because they have direct experience in utilizing academic services. Data were collected through a Likert-based questionnaire and analyzed using descriptive statistics and correlation analysis to examine the relationship between academic service management and student satisfaction. The results of this study are expected to provide an empirical overview of the quality of academic service management at the study program level and the level of student satisfaction as service users. The findings of this study are expected to serve as a basis for evaluation and decision-making in order to continuously improve the quality of academic services and strengthen academic governance oriented towards student satisfaction.